THE ROLE OF GUIDANCE AND COUNSELING TEACHERS IN OPTIMIZING LEARNING MOTIVATION FOR BROKEN HOME - widyaasriningrum; Daulay, Nurussakinah (Jurnal Pendidikan (Teori dan Praktik), 2024)
This research aims to determine the role of guidance and counseling teachers in optimizing the learning motivation of broken home students in class VIII (eight) at the Usman Syarif Tanjung Rejo Islamic Boarding School, Medan Sunggal District, Medan City. A broken home is a condition where a family is not intact, caused by several factors, including divorce and death between couples who are no longer harmonious, where the children are the victims. This research uses field research, namely a type of qualitative research in which the researcher observes and plays a role directly. The two participants in the research included students from broken homes and guidance and counseling teachers who provided services to children from broken homes. Data collection methods used include observation, interviews and documentation methods. Based on the research results, the role of the guidance/counseling teacher as a guide in providing Islamic counseling guidance to students from broken home families is to provide guidance in the form of preventive/prevention, curative/distribution, preservative/repair, and development/development of the function of Islamic counseling guidance. Guidance and counseling teachers provide activities where students experience different motivations from time to time, thereby increasing students' self-confidence and Islamic counseling services play a role by providing, among other things, religious orientation services, religious information services, religious study guidance, and job placement services. and channeling religious talents.